CORNCOB BIOMASS TRANSFORMATION INTO BRIQUETTES BY BUMDES MITRA JAYA: A FEASIBILITY STUDY AND MARKET DEVELOPMENT STRATEGY - Arief Muhazir Insandi; Tampe Tuah Malem Ginting (RADJA PUBLIKA, 2025)
This study analyzes the feasibility and market development strategy of corncob biomass briquette production managed by BUMDes Mitra Jaya. The research was conducted through surveys, interviews with stakeholders, financial analysis, and business strategy formulation using SWOT and Business Model Canvas. The introduction of new machinery increased production capacity from 200 kg/day to 250 kg/day, equivalent to 6,250 kg per month. With an average selling price of IDR 4,000/kg and production costs of IDR 2,500/kg, the net profit increased from IDR 7.5 million to IDR 9.4 million per month. The financial analysis showed a positive Net Present Value (NPV), an Internal Rate of Return (IRR) of around 18–20%, and a Payback Period of about two years, indicating that the business is financially feasible. The SWOT analysis highlighted abundant raw materials and strong local support as major strengths, while technological limitations remained a weakness. Market opportunities included the growing demand for clean energy and household use, with threats from competing briquette industries. The study recommends a competitive pricing strategy, community-based distribution, and digital marketing to strengthen market penetration. The results demonstrate that BUMDes Mitra Jaya can sustainably develop biomass briquettes while contributing to rural economic empowerment and supporting Sustainable Development Goals (SDGs).